Stakeholders Sustenance in Tourism Progression in Ziro Valley of Arunachal Pradesh, India - Thakuria, Vajana (International Journal of Scientific Research and Management (IJSRM), 2017)
The paper focused on the contribution of stakeholders in tourism development in Ziro Valley. The valley is having an enormous potential for tourism development and in fact it is already in the tourism map of Arunachal Pradesh, which attracts both domestic and foreign tourists. Its unique location close to the Talley Valley Wildlife Sanctuary and picturesque landscape, practice of pisci-culture (fish cum paddy) attracts tourists. Ziro valley is the homeland of Apatani tribe of Arunachal Pradesh, famous for their rich culture and traditions. The studies have shown that hospitable and friendly attitudes of locals contribute significantly to overall tourist satisfaction. The study was devised and implemented on the basis of both qualitative and quantitative survey. The survey accounts the contribution and role of the stakeholders for development of tourism in the area.